Association of cytochrome P450 2C19*2 polymorphism with clopidogrel response variability and cardiovascular events in Koreans treated with drug-eluting stents. Issue 2 (23rd June 2011) - Oh, Il-Young; Park, Kyung Woo; Kang, Si-Hyuk; Park, Jin Joo; Na, Sang-Hoon; Kang, Hyun-Jae; Koo, Bon-Kwon; Jeong, Young-Hoon; Hwang, Jin-Yong; Kwak, Choong Hwan; Park, Yongwhi; Hwang, Seok-Jae; et al.
Abstract : Background: Although East Asians carry the cytochrome P450 (CYP) 2C19*2 allele more frequently than do Caucasians, the impact of the CYP2C19*2 allele on clopidogrel pharmacodynamics and clinical outcomes is unknown. Objective: To evaluate the effect of CYP2C19 variants on clopidogrel pharmacodynamics and long-term prognosis in East Asian patients with drug-eluting stents (DES). Methods: DES-treated patients taking dual antiplatelet therapy were enrolled from a Korean multicentre genetic registry. The CYP2C19*2 allele was genotyped using the Taqman method (n=2146), and on-treatment platelet reactivity was measured with the VerifyNow P2Y12 assay (n=1415). Results: 1011 patients (47%) carried at least one CYP2C19*2 allele. The mean on-treatment platelet reactivity was significantly higher in carriers than in non-carriers (250±76 vs 231±83 P2Y12 reaction unit, p<0.001). For up to 12 months' follow-up, the composite of cardiovascular death, non-fatal myocardial infarction and stent thrombosis was significantly higher in carriers of the CYP2C19*2 allele than non-carriers (2.0% vs 0.8%, p=0.02). On landmark analysis, there was no difference in clinical outcome after 12 months between the groups. Conclusion: The CYP2C19*2 genetic variant may be associated with worse outcome in Korean patients treated exclusively with DES and dual-antiplatelet therapy due to a significant increase in cardiac death, myocardial infarction or stent thrombosis.